Penyusunan Sistem Informasi Geografis Amal Usaha Muhammadiyah Bidang Pendidikan Tingkat Menengah di Kabupaten Klaten - Ferdi Pratama, Ferdi Pratama; Putriningsih, Arinda Meilia (Universitas Muhammadiyah Surakarta, 2023)
Muhammadiyah as the largest organization in Indonesia has played an active role in advancing the nation, one of these roles is manifested in the field of education, namely Muhammadiyah schools spread throughout the country. In Klaten District, Muhammadiyah schools have developed quite rapidly. However, Pimpinan Daerah Muhammadiyah (PDM) of Klaten Regency does not yet have a map of the distribution of the Muhammadiyah school, so that the Klaten Regency PDM has difficulty in quickly knowing the distribution of Muhammadiyah schools as a whole. This is the background of the author in building a web-based geographic information system (GIS) for Muhammadiyah schools in Klaten Regency that can be accessed by the Klaten Regency PDM, making it easier to plan for the improvement of Muhammadiyah schools in Klaten Regency. The method used is secondary data analysis and the construction of a web-based geographic information system (GIS). The stages in the development of a web-based geographic information system refer to the System Development Life Cycle (SDLC). The purpose of this study is to provide recommendations to Majelis Pendidikan Dasar Dan Menengah (DIKDASMEN) Pimpinan Daerah Muhammadiyah (PDM) of Klaten Regency regarding which sub-districts need to build a secondary level Muhammadiyah school. The results of this study are in the form of a WebSIG of the distribution of Muhammadiyah schools in Klaten Regency which can be accessed online. From the results, it is known that in Klaten Regency there are 19 Muhammadiyah Middle Schools, 6 Muhammadiyah MTs, 5 Muhammadiyah High Schools, 14 Muhammadiyah Vocational Schools, and 1 Muhammadiyah MA. The sub-districts that are prioritized for the construction of middle-level Muhammadiyah schools are Tulung District or Polanharjo District. With the uneven distribution of Muhammadiyah schools in Klaten Regency, it is necessary to increase educational facilities in Klaten Regency. The system built can be accessed by the general public.